Some algebraic universal semigroup compactifications - H. R. Ebrahimi-Vishki (International Journal of Mathematics and Mathematical Sciences)
Universal compactifications of semitopological semigroups with respect to the properties satisfying the varieties of semigroups and groups are studied through two function algebras.